CHRONIC EXPOSURE TO CARBON MONOXIDE (CO) AND THE MORPHOLOGICAL & MORPHOMETRIC ALTERATIONS OF PULMONARY TISSUE: A COMPARATIVE STUDY - Namozov Elyorbek Ilhom og’li (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Carbon monoxide (CO) is a ubiquitous gas produced by incomplete combustion of carbon‑containing fuels. In Europe and globally, occupational and ambient exposures to CO remain a public health concern. CO binds to haemoglobin, forming carboxyhaemoglobin (COHb) and reducing the oxygen‑carrying capacity of blood, thereby inducing tissue hypoxia. While the acute toxic effects of CO are well documented, less is known about the chronic impact of sustained low‑ to moderate‑level CO exposure on lung morphology and morphometry. The present study seeks to fill this gap by comparing morphological and morphometric indices of lung tissue in controlled animal models and in the light of human epidemiological evidence.